2014
DOI: 10.33549/physiolres.932932
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Levels of the High Mobility Group Box 1 Protein (HMGB1) Are Associated With a Higher Score of Gastrointestinal Dysfunction in Individuals With Autism

Abstract: Autism is a disorder of neural development characterized by impairments in communication, social interaction, restricted interests and repetitive behavior. The etiology of autism is poorly understood, the evidence indicates that inflammation may play a key role. In autism a high prevalence of gastrointestinal disturbances is reported, that are linked to a low-grade chronic inflammation of the intestinal mucosa. High mobility group box 1 protein (HMGB1) is an intranuclear protein that can be passively released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Moreover, research has shown that HMGB1 plasma levels are related to a low concentration of epidermal growth factor (EGF) and higher EGF receptor (EGFR) levels in ASD individuals, suggesting that both EGF and EGFR abnormal levels found in ASD persons may be associated with inflammation and generally increased neuroimmune activity [21,30]. Furthermore, in a study comprising low-functioning ASD individuals aged 2-22 years, plasma HMGB1 levels were found significantly higher in the ASD group than in controls [22]. Additionally, elevated HMGB1 plasma and fecal levels have been associated with higher severity of gastrointestinal (GI) problems in children and young individuals with ASD [22,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, research has shown that HMGB1 plasma levels are related to a low concentration of epidermal growth factor (EGF) and higher EGF receptor (EGFR) levels in ASD individuals, suggesting that both EGF and EGFR abnormal levels found in ASD persons may be associated with inflammation and generally increased neuroimmune activity [21,30]. Furthermore, in a study comprising low-functioning ASD individuals aged 2-22 years, plasma HMGB1 levels were found significantly higher in the ASD group than in controls [22]. Additionally, elevated HMGB1 plasma and fecal levels have been associated with higher severity of gastrointestinal (GI) problems in children and young individuals with ASD [22,31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study comprising low-functioning ASD individuals aged 2-22 years, plasma HMGB1 levels were found significantly higher in the ASD group than in controls [22]. Additionally, elevated HMGB1 plasma and fecal levels have been associated with higher severity of gastrointestinal (GI) problems in children and young individuals with ASD [22,31]. Recent findings of note have shown that HMGB1 may play a role in the stress-induced sensitization of innate immune cells and subsequent neuroinflammation [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in ASD children, there was a strong correlation between HMGB1 and the reduction in plasma epithelial growth factor levels, which was associated with the severity of some symptoms 123 . In addition to core symptoms, higher HMGB1 levels can lead to more severe chronic gastrointestinal dysfunction in children with ASD than those with lower HMGB1 levels 121 . High serum levels of HMGB1 may be biomarkers of the severity of ASD symptoms.…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%
“…Immune dysregulation is thought to be involved in the pathophysiological process of ASD 118,119 . HMGB1 levels are increased in adult and pediatric ASD patients and are independently associated with autism scores that reflect social deficits 120,121 . Monocyte cultures from children with ASD were more sensitive to signaling through selected TLRs, indicating dysfunction in monocyte pathogen recognition and/or TLR signaling pathways 122 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%